2019
DOI: 10.1007/s00704-019-02993-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of temperature time series over the Upper Indus Basin (UIB) Pakistan

Abstract: Runoff generated from the Upper Indus Basin (UIB) mainly originates in the massifs of the Hindukush-Karakoram-Himalaya (HKH) region of Pakistan. Water supply in early spring depends upon the snow accumulation in the winter and the subsequent temperature. Seasonal temperature variations corroborate the contemporary dynamics of snow and glaciers. Recently, there has been increasing evidence of accelerated warming in high mountain areas, termed as elevation-dependent warming (EDW). We have identified trends, anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 69 publications
2
22
1
Order By: Relevance
“…3.3 in any of the Terra or Aqua data. This step significantly improved the snow product, mainly reducing the overestimation in the images captured from offnadir view (Li et al, 2016) and edge-pixels replication due to the broad swath of MODIS (Zeng et al, 2011;Zhang et al, 2017). The cloud cover removed in all the images during the study period by the methodology described from Sect.…”
Section: Merging Terra-and Aqua-filtered Snow Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…3.3 in any of the Terra or Aqua data. This step significantly improved the snow product, mainly reducing the overestimation in the images captured from offnadir view (Li et al, 2016) and edge-pixels replication due to the broad swath of MODIS (Zeng et al, 2011;Zhang et al, 2017). The cloud cover removed in all the images during the study period by the methodology described from Sect.…”
Section: Merging Terra-and Aqua-filtered Snow Productsmentioning
confidence: 99%
“…Also, obscuration of old snow and glacier ice due to their low albedo is challenging for MODIS to capture and is the contributing factor in underestimation of snow and ice cover extent. In contrast, the larger sensor zenith angle (SZA; Li et al, 2016) and low spatial resolution (Hou et al, 2019;Huang et al, 2017) mainly cause overestimation of snow. The overestimation is also significantly influenced by the broad swath of MODIS that amplifies the edge pixels by more than 4 times compared to the pixels at the image centre (Zeng et al, 2011;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding could be explained by enhanced melting from the observed warming during winter [53,54]. The Khunjerab climate station in Hunza, which is located at 4710 m a.s.l., also shows an increasing trend in both annual and seasonal temperatures [21,55]. On the other hand, earlier studies have shown an increasing trend in the SCA [18,24,33].…”
Section: Discussionmentioning
confidence: 69%
“…The major level of confidence associated with these extreme events are related to extreme heat and cold events [ 6 ]. Therefore, the study of temperature variables is a widespread research field [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%